Obstacles of public participation in the design process of public parks / Mohamed Ikhwan Nasir Mohamed Anuar and Masran Saruwono - Mohamed Anuar, Mohamed Ikhwan Nasir; Saruwono, Masran (Faculty of Architechture , Planning & Surveying, 2014)
Designer’s job is no longer to produce unalterable solutions; the fact that there is a need to consult the end users in the design process has been discussed in various literatures. Previous works on public participation have given the depiction of very low public participation. This study is about establishing the obstacles of public participation in the design process of public parks as perceived by landscape architects. Six main factors that are detrimental to public participation were extracted and assessed by representatives from landscape consulting. Data was descriptively analyzed and the results have shed some light regarding the main obstacles.